E-MODULE GUIDED DISCOVERY LEARNING MODEL IN THE HOTS-BASED INDEPENDENT LEARNING CURRICULUM - Rani Darmayanti; Dwi Priyo Utomo; Choirudin Choirudin; Usmiyatun Usmiyatun (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Student's difficulties in learning mathematics independently are due to the lack of media that supports the learning process and is practical in use and the lack of freedom to choose their preferred field. The aim is to develop teaching materials in the form of an e-module guided discovery learning model in the HOTS-based independent learning curriculum. The steps of the Guided Discovery Learning Model used in the e-module are the steps according to Polya, namely: (1) understanding the problem; (2) making plans; (3) implementing the plan; (4) looking back or checking again. This type of research is Research and Development (RND), using development steps according to Borg & Gall, which Sugiyono has transformed. The development steps are limited to seven degrees. Among them; are potential and problems, gathering information, product design, product validation, product improvement, product testing, and product revision. The final result is the percentage of design expert validation getting valid criteria. Moreover, the results of student responses obtained exciting measures. As well as the results of student responses obtaining interesting criteria so that e-modules are feasible to be developed for learning materials